Metaphylaxis of nephrolithiasis in percutaneous nephrolithotripsy: A narrative review - Imzharov, Talgat A.; Zhakiev, Bazylbek S.; Sarkulov, Marat N.; Pavlov, Valentin N.; Mukash, Alisher (Acta Biomedica Atenei Parmensis, 2026)
Background and aim of the work: Urolithiasis (UC) remains a significant global public health concern, with prevalence ranging from 1.2% to 5.3% worldwide and a documented increase of 4.9% between 2017 and 2022. High recurrence rates following surgical treatment contribute substantially to long-term morbidity, healthcare costs, and reduced quality of life. Metaphylaxis has been proposed as a key strategy for preventing recurrent stone formation after percutaneous nephrolithotripsy (PCNL). The aim of this study was to assess the role of metaphylaxis in reducing UC recurrence and improving clinical outcomes after PCNL. Research design and Methods: A narrative literature review was performed using PubMed, Embase, the Cochrane Library, Scopus, Web of Science, and Google Scholar. The search strategy included the terms “urolithiasis,” “nephrolithiasis,” “kidney stones,” “percutaneous nephrolithotripsy,” “recurrence,” and “metaphylaxis.” Meta-analyses, systematic reviews, original studies, and cross-sectional studies published between 2014 and 2024 were included. Non-peer-reviewed and non-evidence-based sources were excluded. In total, 50 peer-reviewed publications in English and Russian were analyzed. Results: The reviewed evidence indicates that metaphylaxis significantly reduces the risk of UC recurrence following PCNL. Patients adhering to individualized dietary and pharmacological recommendations demonstrated a 30–50% reduction in recurrence rates within the first two years. Regular metabolic evaluation enabled early detection and correction of lithogenic risk factors, leading to improved patient-reported outcomes and reduced healthcare utilization. Conclusions: Metaphylaxis represents a fundamental component of modern UC management after PCNL. An integrated approach combining dietary modification, targeted pharmacotherapy, and systematic metabolic monitoring effectively reduces recurrence rates and improves long-term outcomes. Broader implementation of metaphylaxis protocols in routine clinical practice is essential to mitigate the growing global burden of urolithiasis.